Investigating informal development: a case study of Kibera and Sultanbeyli - Runner, Adam D. (Kansas State University, 2011)
As global development trends continue, planners and social scientists of the future will have an increasingly pressing responsibility to effectively and sensitively address and interact with informal development. This report seeks to provide theoretical research to expand the knowledge base of planners and social scientists with respect to informal development. It aims to begin to explore and explain how informal development and living conditions interact, and to understand what the role of the planner and social scientist should be in interfacing with informal development in the future. Through case study this report considers two distinct typologies of informal settlements in order to compare and contrast factors in each settlement‘s history and development, living conditions, and overarching administrative relationships to identify trends in the development and manifestation of informal settlements.
Keywords: Informal settlements; Urban planning; Land use planning; Environmental Studies (0477)